Development of SSR markers for the tropical alpine tree species Leptospermum recurvum (Myrtaceae) on Mount Kinabalu in Borneo1. (2nd September 2013) - Ando, Soichi; Kaneko, Shingo; Isagi, Yuji; Repin, Rimi; Kitayama, Kanehiro
Abstract : Premise of the study: Nuclear microsatellite (simple sequence repeat [SSR]) markers were developed for the woody species Leptospermum recurvum found on Mount Kinabalu, Borneo, to facilitate investigation of the genetic structure and patterns of gene flow in relation to leaf phenotypic polymorphisms. Methods and Results: Eleven primer pairs were developed using the compound SSR marker technique. Ten of the 11 loci were polymorphic and their expected heterozygosity ranged from 0.04 to 0.83. Neither linkage disequilibrium nor departure from Hardy–Weinberg equilibrium were detected. All primer pairs also amplified the SSR loci of L. polygalifolium . Conclusions: These findings suggest the utility of these primers for investigating genetic structure and gene flow in L. recurvum and indicate their applicability to another species of Leptospermum .